2022
DOI: 10.3390/e24101358
|View full text |Cite
|
Sign up to set email alerts
|

Automated Caries Screening Using Ensemble Deep Learning on Panoramic Radiographs

Abstract: Caries prevention is essential for oral hygiene. A fully automated procedure that reduces human labor and human error is needed. This paper presents a fully automated method that segments tooth regions of interest from a panoramic radiograph to diagnose caries. A patient’s panoramic oral radiograph, which can be taken at any dental facility, is first segmented into several segments of individual teeth. Then, informative features are extracted from the teeth using a pre-trained deep learning network such as VGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition to these methods, hybrid methods combined with two different algorithms were also used. CNN-LSTM [70], CNN-SVM [71], Siamese Network-DenseNet121 [71], and CNN-fuzzy logic [84] are hybrid models using. In a study [74], a swine transformer, one of the transformer types shown to compete with CNNs recently, was used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these methods, hybrid methods combined with two different algorithms were also used. CNN-LSTM [70], CNN-SVM [71], Siamese Network-DenseNet121 [71], and CNN-fuzzy logic [84] are hybrid models using. In a study [74], a swine transformer, one of the transformer types shown to compete with CNNs recently, was used.…”
Section: Resultsmentioning
confidence: 99%
“…used SVM to automatically segment the tooth region of interest from panoramic radiographs for dental caries diagnosis, revealing that the method had an accuracy of 93.58 %, sensitivity of 93.91 %, and specificity of 93.33 %, indicating promising potential for a wider application. 28 The advancements in these emerging technologies are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Various CNN-based structures have been proposed and applied in semantic segmentation, of which fully convolutional networks (FCNs) that have an encoder–decoder structure are a milestone [ 17 ]. Since then, several types of CNN architectures, such as ResNet [ 18 ], ResNext [ 19 ], VGG [ 20 ], and GoogleNet [ 21 ], have been used as encoders and decoders. U-net [ 22 ] is based on FCN [ 23 ] and exhibits the advantages of good performance, low data requirement, and high speed.…”
Section: Introductionmentioning
confidence: 99%